The impact of high-intensity interval training on vascular function in adults: A systematic review and meta-analysis - Khalafi, Mousa; Sakhaei, Mohammad Hossein; Kazeminasab, Fatemeh; Symonds, Michael E.; Rosenkranz, Sara K. (Frontiers in Cardiovascular Medicine, 2022)
Aim We performed a systematic review and meta-analysis to investigate the effects of high-intensity interval training (HIIT) compared with moderate-intensity continuous training (MICT) or with no exercise (CON) on vascular function in adults who were free of cardiometabolic diseases and those with cardiometabolic diseases. Method A search across three electronic databases including Scopus, PubMed, and Web of Science was conducted through February 2022 to identify the randomized trials evaluating HIIT versus MICT and/or CON on vascular function as measured using brachial artery flow-mediated dilation (FMD) in adults. Separate analyses were conducted for HIIT versus MICT and/or CON to calculate weighted mean differences (WMD) and 95% confidence intervals (95% CIs) using random or fixed models. Results A total of 36 studies involving 1437 participants who were either free of cardiometabolic diseases or had cardiometabolic diseases were included in the meta-analysis. HIIT effectively increased FMD when compared with MICT [1.59% (95% CI 0.87 to 2.31), p=0.001] or CON [3.80% (95% CI 2.58 to 5.01), p=0.001]. Subgroup analysis showed that HIIT increased FMD in participants with cardiovascular and metabolic diseases, but not in participants who were free of cardiometabolic diseases. In addition, HIIT effectively increased FMD regardless of age and BMI. Conclusion We confirm that HIIT is effective for improving vascular function in individuals with metabolic disorders and cardiovascular diseases and has a superior effect compared to MICT, demonstrating time efficiency.